Development of HTTP Server for Remote Data Monitoring and Recording System - Singh, D Joseph Sunder; Padmalatha, Mrs. L. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper focuses on development of remote data monitoring and recording system in industries. Now a days we are using many Networked embedded systems for monitoring and control the home or industrial devices.These low cost devices are capable of reporting and receiving information in just the same way that computers on a network. The advent of Internet communication standard, TCP/IP, offers significant potential in terms of remote monitoring and management of construction sites using embedded systems. In this paper the design method of low cost system of remote data monitoring, and recording is designed based on ARM. For this a small HTTP SERVER is built in LPC2148 and it is connected with the remote monitoring terminal through Ethernet. The data can be stored in the SD Card via SPI interface. At the same time, for the sake of the versatility, the FAT file system is built in the SD Card. So, an Ethernet-enabled remote data monitoring system with the ability of data recording is built. This design is having advantage of cost-effective, easily realized, stable and reliable transmission. It can be connected to the INTERNET or LAN through TCP/IP protocol. FreeRTOS is used as an operating system running on ARM processor, an industrial grade RTOS for hard time applications. By this design the data is sent without a PC and system favour’s large scale data acquisition system.